1998
DOI: 10.1021/bc9701510
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Interpolyelectrolyte Complexes between Double-Stranded DNA and Polylysine Comb-Type Copolymers Having Hydrophilic Side Chains

Abstract: The polyionic interaction between DNA and polycations grafted with hydrophilic dextran side chains was evaluated. The comb-type copolymers, poly(L-lysine)-graft-dextran, were successfully prepared by employing a reductive amination reaction between epsilon-amino groups of poly(L-lysine) (PLL) and the reductive ends of dextran (Dex). A coupling efficacy on the order of 70% was obtained regardless of intrinsic philicities of the solvents used, either aqueous buffer or DMSO. The resulting graft copolymers, which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
118
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 120 publications
(127 citation statements)
references
References 30 publications
(40 reference statements)
5
118
0
Order By: Relevance
“…Aminated dextran was prepared as described by Maruyama et al 15 with minor modifications. Dextran 180 mg was dissolved in dimethyl sulfoxide, and sodium cyanoborohydride (189 mg, 3 mM) was added.…”
Section: Synthesis Of Dexblg Block Copolymermentioning
confidence: 99%
“…Aminated dextran was prepared as described by Maruyama et al 15 with minor modifications. Dextran 180 mg was dissolved in dimethyl sulfoxide, and sodium cyanoborohydride (189 mg, 3 mM) was added.…”
Section: Synthesis Of Dexblg Block Copolymermentioning
confidence: 99%
“…We have been interested in soluble complex formation observed with cationic graft copolymers containing poly(Llysine) and dextran, PLL-g-Dex ( Figure 1); PLL-g-Dex has a polycation backbone and hydrophilic side chains. 2 The copolymer with a high degree of grafting forms totally soluble DNA complexes without inducing collapse. 3 We have shown that PLL-g-Dex increases stability of DNA hybrids, 2 accelerates DNA hybridization, 4 and activates DNA strand-exchange reactions.…”
mentioning
confidence: 99%
“…2 The copolymer with a high degree of grafting forms totally soluble DNA complexes without inducing collapse. 3 We have shown that PLL-g-Dex increases stability of DNA hybrids, 2 accelerates DNA hybridization, 4 and activates DNA strand-exchange reactions. 5 However, interaction of the copolymer with DNA is not thoroughly understood and the influence of the copolymer grafting degree on conformation of DNA has not been assessed.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The carbohydrate lactose molecules conjugated to the polycation poly(L-lysine) can work as solubilizer 10 of the DNA polyion complexes and weaken the electrostatic interaction between the phosphate groups of DNA and the amino groups of poly(L-lysine). The protonated imidazole groups of PLH-NH 2 are considered to have taken the phosphate groups of DNA from the amino groups of PLL-Lac.…”
mentioning
confidence: 99%